(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3GdebGdI GdKGdKI ef cJGH cGed GdUfGYI ai GdMejGJ hGdChQGe hgj CQHYI hKdGKhf HGHG s
(3BNQgG (B:s
(3cedJ GdebGdI GdNGeSI ef GdLRA GdKGfi ef GdYed ef cJGH cGed GdUfGYI GdWHjI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B109 - (3U(B253s
(3GfXQgG eY GdJUQja def YLR GdJCdja Qbe (B391 -400"s
(3bWYI ef fSNI JGSYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B193 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B328 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs